Effects of Using Cassava Leaf Powder on Quail Growth Performance at National University of Cheasim Kamchaymear, Cambodia - Heng, Sophea; Choeurn, Kan; Keo, Chanraksmey; SEREY, Mardy (AgriMalS, 2025)
Quail are a popular domestic breed, easy to raise, fast-growing, and prolific egg producers. They also exhibit high resistance to diseases. Feed is a crucial factor in animal husbandry; utilizing high-value feed directly correlates with lower profits. This study aims to evaluate the effect of cassava leaf powder as a feed on the quail's growth performance. This experiment was conducted at Thnalkaeng village, Smaongcheung commune, Kamchaymear district, Prey Veng province. For this study's methods, 180 healthy 4-day-old quails, with an average weight of 10.20 grams, were selected and randomly assigned to four treatments (T0, T1, T2, and T3). Each treatment comprised three replicates, with 15 quail per replicate, following a completely randomized design (CRD) experimental model. Treatment T0 received 100% compound feed (control). Treatment T1 received 5% cassava leaf powder and 95% compound feed. Treatment T2 received 10% cassava leaf powder and 90% compound feed. Treatment T3 received 15% meat meal and 85% compound feed. In this experiment, all quails were weighed at the beginning and then weekly from the first to the sixth week. The results showed no statistically significant difference (P > 0.05) in the average daily feed intake among the quail. However, the intake of quails in treatment T2 (15.76 g) was higher. The average starting weight of all quails was similar (P>0.05). A statistically significant difference (P<0.05) was observed in the average daily weight gain during the first week. Conversely, the daily weight gain from the second to the sixth week did not differ significantly (P>0.05) among the quail. The average daily weight gain was highest in quails from treatment T1 (3.64 g), which were fed cassava leaf powder at a 5% level. No significant difference (P>0.05) was found in the average feed conversion ratio (FCR) among the quail. Quails in treatment T1 exhibited the lowest feed conversion ratio (4.48 g). Based on the results of this study, it can be concluded that adding cassava leaf powder to the feed does not positively affect daily feed intake or the feed conversion ratio. However, using cassava leaf powder at a 5% level does have a positive effect on weight gain.